IOT-BASED SMART HELMET WITH INTEGRATED WIRELESS COMMUNICATION FOR HAZARD DETECTION AND WORKER SAFETY - Maryam Salim Ali (Journals Park Publishing, 2025)
In hazardous places like mining, building stuff, and getting oil out of the ground, workers often deal with gases that aren't good for them. This idea is for a cool helmet that's super smart and can tell if there are any of those bad gases around. It uses some techy IoT stuff. This helmet isn't just about keeping your head safe from bumps; it's got some clever features too. Like, it knows when you put it on and starts working without you having to do anything. It tells your boss where you are and if there's smoke nearby. It's got buttons to let them know when you're done with a job. So, when you wear it, it's like having a little buddy that keeps an eye on things for you. Leveraging IoT and GPS technologies, the system continuously transmits real-time environmental and location data to a centralized monitoring platform, enabling remote supervision and rapid emergency response. The primary objective of this design is to improve workplace safety by ensuring immediate communication of critical incidents and precise worker tracking. In emergencies, this cool helmet lets workers send their exact location to the big boss on site. It's like having a homing beacon for when things go haywire! This little experiment shows that fancy gadgets you wear can really up the safety game in jobs where it's super risky.
Keywords: Smart Helmet, IoT Gas, Detection, Real-Time Monitoring, Toxic Gas Sensors.